Validation of a UV Spectrometric Method for the Assay of Tolfenamic Acid in Organic Solvents. (10th December 2015) - Ahmed, Sofia; Mustaan, Nafeesa; Sheraz, Muhammad Ali; Nabi, Syeda Ayesha Ahmed un; Ahmad, Iqbal
Abstract : The present study has been carried out to validate a UV spectrometric method for the assay of tolfenamic acid (TA) in organic solvents. TA is insoluble in water; therefore, a total of thirteen commonly used organic solvents have been selected in which the drug is soluble. Fresh stock solutions of TA in each solvent in a concentration of 1 × 10 −4  M (2.62 mg%) were prepared for the assay. The method has been validated according to the guideline of International Conference on Harmonization and parameters like linearity, range, accuracy, precision, sensitivity, and robustness have been studied. Although the method was found to be efficient for the determination of TA in all solvents on the basis of statistical data 1-octanol, followed by ethanol and methanol, was found to be comparatively better than the other studied solvents. No change in the stock solution stability of TA has been observed in each solvent for 24 hours stored either at room (25 ± 1 °C) or at refrigerated temperature (2–8°C). A shift in the absorption maxima has been observed for TA in various solvents indicating drug-solvent interactions. The studied method is simple, rapid, economical, accurate, and precise for the assay of TA in different organic solvents.